Flame-retardant fiber curtain fabric and preparation method thereof
By using flame retardants such as nanosilicon dioxide and nanomagnesium hydroxide on fiber curtain fabrics, combined with catalysts and self-healing coatings, a multifunctional composite coating is formed, which solves the insufficient flame retardant effect of existing flame retardant materials at high temperatures. and poor durability, efficient flame retardant performance and thermal stability are achieved.
Patent Information
- Application Number
- CN202411710422.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing flame retardant materials may degrade during long-term use, release harmful gases, and have insufficient flame retardant effect at high temperatures, poor durability, and lack self-repair function, which limits their application range.
Using nanosilicon dioxide and nanomagnesium hydroxide as synergistic flame retardants, combined with catalyst and self-healing coatings to form a multifunctional composite coating, providing physical barriers, catalytic reactions and self-healing functions, enhancing flame retardant performance and thermal stability .
It significantly improves the flame retardant effect, reduces the release of toxic gases, extends the service life of the material, and provides a lasting protection effect in high temperature environments.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fabrics, in particular to a flame-retardant fiber curtain fabric and a preparation method thereof. Background Art
[0002] As people pay more attention to safety in their daily lives, fireproof and flame-retardant materials are increasingly used in various fields, especially in the home furnishing, textile, construction, and automotive industries. However, existing flame-retardant materials generally have shortcomings such as limited flame retardancy, poor durability, aging problems during use, and the potential release of toxic gases at high temperatures.
[0003] Currently, commonly used flame-retardant materials on the market fall into two main categories: those based on chemical flame retardants and those whose flame-retardant properties are enhanced through changes in their physical structure. Chemical flame retardants typically include phosphorus-, nitrogen-, and chlorine-based chemicals. These materials inhibit combustion through various mechanisms, such as releasing flammable gases or forming a protective carbon layer. However, these materials may degrade over time and even release harmful gases such as hydrogen chloride and carbon monoxide in the event of a fire, causing secondary pollution. Furthermore, chemical flame retardants may affect fibers or other substrates, reducing their mechanical properties or weather resistance.
[0004] While materials with physically reinforced flame retardancy, such as glass fiber and inorganic coatings, can provide some thermal protection, their flame retardancy is often insufficient to withstand the direct effects of high-temperature flames. Furthermore, the weight and rigidity of the materials themselves may limit their application. These materials also often lack self-healing properties, leading to breakage or performance degradation over time.
[0005] Furthermore, most existing flame-retardant coatings use a single flame-retardant component, failing to fully utilize the synergistic effects of different flame-retardant ingredients. Under extreme high temperatures, the performance of flame-retardant coatings may be affected by factors such as localized failure, coating peeling, or deformation, making them unable to continuously and effectively prevent the spread of fire.
[0006] Therefore, the existing flame retardant technology has certain limitations, and there is an urgent need to develop a more efficient, stable and durable multifunctional flame retardant material to meet the high requirements for material safety and long-term stability in fire accidents. Summary of the Invention
[0007] In view of the shortcomings of the prior art, the object of the present invention is to provide a flame retardant fiber curtain fabric and a preparation method thereof.
[0008] The above-mentioned object of the present invention is achieved through the following technical solutions: A flame-retardant fiber curtain fabric comprises a fabric base and a flame-retardant coating arranged on the fabric base, wherein the flame-retardant coating comprises nano silicon dioxide particles and nano magnesium hydroxide particles in a mass ratio of 1:1.2-2.
[0009] The present invention introduces two flame retardants, nano-silicon dioxide and nano-magnesium hydroxide, to form a synergistic flame retardant mechanism. Silicon dioxide acts as a barrier layer to provide a physical barrier, while magnesium hydroxide decomposes at high temperatures to produce water vapor, cooling and diluting the flame.
[0010] Furthermore, a catalyst coating and a self-repairing coating are further provided on the flame retardant coating, and the catalyst coating is prepared by including the following components in parts by weight: 2-4 parts of titanium dioxide; 1-2 parts of zirconium phosphate; 0.3-0.8 parts of coupling agent; 1-3 parts of polyvinyl alcohol; 90-95 parts of deionized water.
[0011] A catalytic coating is a functional coating that decomposes harmful substances, releases flame-retardant gases, or promotes the formation of a carbon layer through catalytic reactions in high-temperature or flame environments. Under high-temperature conditions, the catalytic coating promotes flame-retardant reactions, accelerating decomposition or polymerization reactions to form a protective layer, reducing the flammability of the material. The catalytic coating can reduce the release of toxic gases (such as carbon monoxide and hydrogen cyanide) during combustion, reducing smoke and toxicity. When exposed to flames, the catalytic coating promotes carbonization, forming a dense, protective carbon layer that acts as a heat and oxygen barrier, slowing the spread of flames. Specifically, under high-temperature conditions, titanium dioxide accelerates the pyrolysis of organic materials, generating non-flammable gases (such as water vapor and carbon dioxide) and creating a carbon-rich structure on the surface. The zirconium phosphate component in the catalytic coating decomposes at high temperatures to produce acidic substances, which catalyze the rapid dehydration and carbonization of the underlying material. By lowering the pyrolysis temperature, inhibiting free radical reactions, and promoting carbon layer formation, the catalytic coating significantly enhances flame retardancy and reduces the release of toxic smoke and gases.
[0012] Furthermore, the self-repairing coating comprises the following components in parts by weight: 8-12 parts of polyethylene glycol; 3-5 parts of furan-based polyamide elastomer; 30-50 parts of dimethylformamide; 9-11 parts of bismaleimide resin; 4 to 6 parts of ammonium polyphosphate.
[0013] When a self-healing phase-change coating, a catalytic coating, and a flame retardant layer are stacked together, the resulting multifunctional composite coating exhibits excellent flame retardancy and thermal protection. The coating comprises a bottom layer of flame retardants containing nano-silica particles and nano-magnesium hydroxide; a middle layer of catalytic coatings containing titanium dioxide and zirconium phosphate; and a top layer of a self-healing phase-change coating containing a thermoresponsive polymer and phase-change material. These layers work synergistically to provide multiple flame-retardant mechanisms at high temperatures, slowing flame propagation and improving the thermal stability of the material. The phase-change material in the top layer, such as polyethylene glycol (PEG), absorbs heat and melts at its phase transition point, slowing heat transfer and delaying the substrate from reaching combustion temperature, creating a window for activation of the underlying flame retardant and catalytic coating. At high temperatures, the catalytic coating promotes the decomposition of the flame retardant and captures free radicals (such as OH· and H·) in the flame, interrupting the combustion chain reaction, effectively suppressing flame propagation and reducing the release of toxic gases such as carbon monoxide. Catalytic components such as zirconium phosphate release acidic substances that further catalyze the carbonization of the substrate, forming a dense carbon layer that provides additional protection. The self-healing polymer softens and flows at high temperatures, repairing cracks caused by heat or physical damage, ensuring the integrity of the coating and extending the service life of the material. Ultimately, the composite coating blocks heat and oxygen through the carbonized barrier, enhancing overall protection and achieving long-lasting flame retardancy.
[0014] Furthermore, the nano-silicon dioxide particles and nano-magnesium hydroxide particles are both modified by a silane coupling agent.
[0015] Furthermore, the thickness of the flame retardant coating is controlled to be 300-400 μm.
[0016] Furthermore, the thickness of the catalyst coating is controlled to be 100-200 μm.
[0017] Furthermore, the thickness of the self-repairing coating is controlled to be 200-300 μm.
[0018] The thickness of the flame-retardant coating provides sufficient material to ensure the flame retardant fully exerts its flame-retardant properties. Within this range, the coating effectively slows the spread of flames at high temperatures and forms a thermal barrier, preventing the substrate from rapidly heating up. A thicker flame-retardant layer also provides longer-lasting protection, making the flame-retardant reaction more stable and durable. Keeping the catalyst coating thickness between 100 and 200 μm optimizes the efficiency of the catalytic reaction. This range ensures that the catalyst effectively accelerates the decomposition of the flame retardant and promotes the formation of a carbonized layer at high temperatures. If the thickness is too thin, the catalyst may not cover the entire surface and provide uniform catalytic action. Too thick may cause cracking or overburden the coating, affecting overall adhesion and stability. Keeping the self-healing coating thickness between 200 and 300 μm helps ensure that the coating can effectively soften and flow under high-temperature conditions, filling any cracks or damage. This thickness provides sufficient polymer and phase change material to perform its repair and heat-absorbing functions. If the thickness is too low, the repair capacity may not be sufficient to cover all defects. Excessive thickness may affect the coating's response speed and mechanical properties.
[0019] Furthermore, 0.5 to 1.5 parts by weight of borate is added to the catalyst coating.
[0020] Borates enhance catalyst performance through a variety of mechanisms. They can modulate the acidity and alkalinity of the catalyst surface, forming acidic or alkaline active sites, thereby optimizing catalytic conditions and enhancing catalytic reaction activity. Borates form complexes with metal oxides, improving the surface structure and increasing the number of active sites, thereby enhancing catalytic performance. Furthermore, borates exhibit high thermal stability, inhibiting sintering at high temperatures and maintaining high catalyst activity and long-term performance. By adjusting the electron density on the catalyst surface, borates can also optimize electron transfer pathways and enhance electron transport during reactions. Borates can also regulate the concentration of oxygen vacancies, thereby enhancing catalyst activity in redox reactions. Furthermore, borates can sometimes affect the catalyst's crystalline structure, regulating phase transitions and increasing the specific surface area and active surface region, further improving reaction efficiency.
[0021] Furthermore, 0.1 to 0.3 parts by weight of copper oxide is added to the self-repairing coating.
[0022] The introduction of copper oxide can enhance the coating's catalytic activity and heat resistance, especially at high temperatures. Titanium dioxide and borates are already used in catalyst coatings, and the addition of similar substances like copper oxide can help strengthen the synergistic effect between the different coatings. These components work together to significantly improve the coating's thermal stability and catalytic performance. Copper oxide not only promotes redox reactions but also increases active sites, improving the coating's performance at high temperatures.
[0023] Furthermore, copper oxide, as a transition metal oxide, has the ability to modulate surface acidity and alkalinity, a property that complements the effects of borates. The combination of the two can more effectively adjust the acid-base balance on the catalyst surface, improving catalytic efficiency. This is particularly important in reactions involving acid-base catalysis, as such adjustments can provide a more optimal catalytic environment.
[0024] The introduction of transition metal oxides also optimizes electron transport pathways, enhancing the efficient transfer of electrons during the catalytic process. This optimization increases electron mobility during the reaction, thereby improving the overall catalytic efficiency of the coating. At high temperatures, the transition metal oxides and borates work together to inhibit catalyst sintering, maintaining the activity and stability of the coating surface and extending its service life.
[0025] During the self-healing coating's repair process, these components work synergistically, not only helping to repair the coating's physical structure but also enhancing its catalytic performance during the repair process. Copper oxide and other transition metal oxides accelerate the recovery of catalytic reactions, allowing the repaired coating to maintain its efficient catalytic activity.
[0026] A method for preparing the flame-retardant fiber curtain fabric comprises the following steps: S1: Mix nano-silica and magnesium hydroxide evenly, add an appropriate amount of dispersant, and stir using a high-speed shear emulsifier for 10 minutes; immerse the fabric substrate in the flame retardant dispersion for 20 minutes, remove and scrape off excess solution; preliminarily dry at 100°C, and then cure at 150°C for 30 minutes; S2: After mixing and stirring the various components of the catalyst coating in proportion, the catalyst coating is applied to the surface of the fabric treated in step S1 by brushing or dipping at 100°C for 20 minutes; S3: After mixing the various components of the catalyst coating in proportion, stir at a low speed for 2 to 3 hours, then let it stand and mature for 1 to 2 hours, use a spraying device to evenly spray the solution on the fabric treated in step S1, and place it in an oven at 60 to 100°C to dry for 1 to 2 hours.
[0027] Compared with the prior art, the beneficial effects of the present invention are mainly reflected in the following aspects: First, by introducing nano-silica and nano-magnesium hydroxide as flame retardants, a synergistic flame-retardant mechanism is formed. Silica provides a physical barrier, preventing the transfer of heat and oxygen, while magnesium hydroxide decomposes at high temperatures to produce water vapor, which cools and dilutes the flame, significantly enhancing the flame retardant effect. Second, the introduction of a catalyst coating enables the coating to promote flame retardant reactions in high-temperature environments, decomposing harmful substances, releasing non-combustible gases, and promoting the formation of a carbon layer, effectively delaying the spread of flames and reducing the release of toxic smoke and gases.
[0028] Furthermore, the catalytic coating of the present invention, particularly the combination of titanium dioxide and zirconium phosphate, not only accelerates the pyrolysis reaction but also generates acidic substances that catalyze the dehydration and carbonization of the underlying material, thereby forming a dense carbon layer and enhancing flame retardancy. The catalytic coating also captures free radicals during combustion, inhibiting the combustion chain reaction and further reducing the propagation of flames.
[0029] The incorporation of a self-healing coating is another significant advantage of this invention. This coating softens and flows under high-temperature conditions, filling cracks caused by heat or physical damage, thereby maintaining the coating's integrity and ensuring sustained protection. The combination of a self-healing polymer and phase-change material absorbs heat, delaying the substrate from reaching combustion temperature and providing a window for activation of the underlying flame-retardant and catalytic coatings.
[0030] Overall, the multifunctional composite coating of the present invention significantly improves the flame retardancy and thermal stability of fiber fabrics through synergistic effects. The combination of coating layers ensures the effectiveness of multiple protection mechanisms, resulting in excellent flame retardancy in high-temperature environments, reduced toxic gas emissions, and extended material life. DETAILED DESCRIPTION
[0031] The present invention is described in detail below with reference to the embodiments.
[0032] Example 1 A flame-retardant fiber curtain fabric comprises a fabric base and a flame-retardant coating arranged on the fabric base, wherein the flame-retardant coating comprises nano silicon dioxide particles and nano magnesium hydroxide particles in a mass ratio of 1:1.2.
[0033] A method for preparing the flame-retardant fiber curtain fabric comprises the following steps: S1: Mix nano-silica and magnesium hydroxide evenly, add appropriate amount of dispersant, and stir using a high-speed shear emulsifier for 10 minutes; immerse the fabric base in the flame retardant dispersion for 20 minutes, remove and scrape off excess solution; preliminarily dry at 100°C, and then cure at 150°C for 30 minutes.
[0034] Example 2 A flame-retardant fiber curtain fabric comprises a fabric base and a flame-retardant coating arranged on the fabric base, wherein the flame-retardant coating comprises nano silicon dioxide particles and nano magnesium hydroxide particles in a mass ratio of 1:1.6.
[0035] A method for preparing the flame-retardant fiber curtain fabric comprises the following steps: S1: Mix nano-silica and magnesium hydroxide evenly, add appropriate amount of dispersant, and stir using a high-speed shear emulsifier for 10 minutes; immerse the fabric base in the flame retardant dispersion for 20 minutes, remove and scrape off excess solution; preliminarily dry at 100°C, and then cure at 150°C for 30 minutes.
[0036] Example 3 A flame-retardant fiber curtain fabric comprises a fabric base and a flame-retardant coating arranged on the fabric base, wherein the flame-retardant coating comprises nano silicon dioxide particles and nano magnesium hydroxide particles in a mass ratio of 1:2.
[0037] A method for preparing the flame-retardant fiber curtain fabric comprises the following steps: S1: Mix nano-silica and magnesium hydroxide evenly, add appropriate amount of dispersant, and stir using a high-speed shear emulsifier for 10 minutes; immerse the fabric base in the flame retardant dispersion for 20 minutes, remove and scrape off excess solution; preliminarily dry at 100°C, and then cure at 150°C for 30 minutes.
[0038] Example 4 A flame-retardant fiber curtain fabric comprises a fabric base and a flame-retardant coating arranged on the fabric base, wherein the flame-retardant coating comprises nano silicon dioxide particles and nano magnesium hydroxide particles in a mass ratio of 1:2.
[0039] A method for preparing the flame-retardant fiber curtain fabric comprises the following steps: S1: Nano-silica and nano-magnesium hydroxide were placed separately in deionized water containing a silane coupling agent (KH-550) and ultrasonically treated for 30 minutes to achieve uniform dispersion and surface modification. The modified nano-silica and magnesium hydroxide solutions were then mixed evenly, an appropriate amount of dispersant was added, and the mixture was stirred using a high-speed shear emulsifier for 10 minutes. The fabric substrate was immersed in the flame-retardant dispersion for 20 minutes, removed and the excess solution scraped off. The fabric was initially dried at 100°C and then cured at 150°C for 30 minutes. Both the nano-silica and nano-magnesium hydroxide particles were modified with a silane coupling agent.
[0040] Example 5 A flame-retardant fiber curtain fabric comprises a fabric base and a flame-retardant coating, a catalyst coating and a self-repairing coating sequentially arranged on the fabric base, wherein the flame-retardant coating comprises nano-silicon dioxide particles and nano-magnesium hydroxide particles in a mass ratio of 1:2.
[0041] The catalyst coating is prepared by including the following components in parts by weight: 2 parts of titanium dioxide; 1 part zirconium phosphate; 0.3 parts of coupling agent; 1 part of polyvinyl alcohol; 90 parts of deionized water.
[0042] The self-repairing coating includes the following components in parts by weight: 8 parts of polyethylene glycol; 3 parts of furan-based polyamide elastomer; 30 parts of dimethylformamide; 9 parts of bismaleimide resin; 4 parts of ammonium polyphosphate.
[0043] The thickness of the flame retardant coating is controlled to be 300 μm.
[0044] The thickness of the catalyst coating is controlled to be 100 μm.
[0045] The thickness of the self-repairing coating is controlled to be 200 μm.
[0046] A method for preparing the flame-retardant fiber curtain fabric comprises the following steps: S1: Nano-silica and nano-magnesium hydroxide were placed separately in deionized water containing a silane coupling agent (KH-550) and ultrasonically treated for 30 minutes to achieve uniform dispersion and surface modification. The modified nano-silica and magnesium hydroxide solutions were then mixed evenly, an appropriate amount of dispersant was added, and the mixture was stirred using a high-speed shear emulsifier for 10 minutes. The fabric substrate was immersed in the flame-retardant dispersion for 20 minutes, removed and the excess solution scraped off. The fabric was initially dried at 100°C and then cured at 150°C for 30 minutes. Both the nano-silica and nano-magnesium hydroxide particles were modified with a silane coupling agent.
[0047] S2: After mixing and stirring the various components of the catalyst coating in proportion, the catalyst coating is applied to the surface of the fabric treated in step S1 by brushing or dipping at 100°C for 20 minutes; S3: After mixing the various components of the catalyst coating in proportion, stir at low speed for 2 hours, then let it stand and mature for 2 hours, use a spraying device to evenly spray the solution on the fabric treated in step S1, and place it in a 60°C oven to dry for 2 hours.
[0048] Example 6 A flame-retardant fiber curtain fabric comprises a fabric base and a flame-retardant coating, a catalyst coating and a self-repairing coating sequentially arranged on the fabric base, wherein the flame-retardant coating comprises nano-silicon dioxide particles and nano-magnesium hydroxide particles in a mass ratio of 1:2.
[0049] The catalyst coating is prepared by including the following components in parts by weight: 4 parts of titanium dioxide; 2 parts of zirconium phosphate; 0.8 parts of coupling agent; 3 parts of polyvinyl alcohol; 95 parts of deionized water.
[0050] The self-repairing coating includes the following components in parts by weight: 12 parts of polyethylene glycol; 5 parts of furan-based polyamide elastomer; 50 parts of dimethylformamide; 11 parts of bismaleimide resin; 6 parts of ammonium polyphosphate.
[0051] The thickness of the flame retardant coating is controlled to be 400 μm.
[0052] The thickness of the catalyst coating is controlled to be 200 μm.
[0053] The thickness of the self-repairing coating is controlled to be 300 μm.
[0054] A method for preparing the flame-retardant fiber curtain fabric comprises the following steps: S1: Nano-silica and nano-magnesium hydroxide were placed separately in deionized water containing a silane coupling agent (KH-550) and ultrasonically treated for 30 minutes to achieve uniform dispersion and surface modification. The modified nano-silica and magnesium hydroxide solutions were then mixed evenly, an appropriate amount of dispersant was added, and the mixture was stirred using a high-speed shear emulsifier for 10 minutes. The fabric substrate was immersed in the flame-retardant dispersion for 20 minutes, removed and the excess solution scraped off. The fabric was initially dried at 100°C and then cured at 150°C for 30 minutes. Both the nano-silica and nano-magnesium hydroxide particles were modified with a silane coupling agent.
[0055] S2: After mixing and stirring the various components of the catalyst coating in proportion, the catalyst coating is applied to the surface of the fabric treated in step S1 by brushing or dipping at 100°C for 20 minutes; S3: After mixing the various components of the catalyst coating in proportion, stir at low speed for 3 hours, then let it stand and mature for 1 hour, use a spraying device to evenly spray the solution on the fabric treated in step S1, and place it in an oven at 100°C to dry for 1 hour.
[0056] Example 7 A flame-retardant fiber curtain fabric comprises a fabric base and a flame-retardant coating, a catalyst coating and a self-repairing coating sequentially arranged on the fabric base, wherein the flame-retardant coating comprises nano-silicon dioxide particles and nano-magnesium hydroxide particles in a mass ratio of 1:2.
[0057] The catalyst coating is prepared by including the following components in parts by weight: 3 parts of titanium dioxide; 1.5 parts of zirconium phosphate; 0.5 parts of coupling agent; 2 parts of polyvinyl alcohol; 93 parts of deionized water.
[0058] The self-repairing coating includes the following components in parts by weight: 10 parts of polyethylene glycol; 4 parts of furan-based polyamide elastomer; 40 parts of dimethylformamide; 10 parts of bismaleimide resin; 5 parts of ammonium polyphosphate.
[0059] The thickness of the flame retardant coating is controlled to be 350 μm.
[0060] The thickness of the catalyst coating is controlled to be 150 μm.
[0061] The thickness of the self-repairing coating is controlled to be 250 μm.
[0062] A method for preparing the flame-retardant fiber curtain fabric comprises the following steps: S1: Nano-silica and nano-magnesium hydroxide were placed separately in deionized water containing a silane coupling agent (KH-550) and ultrasonically treated for 30 minutes to achieve uniform dispersion and surface modification. The modified nano-silica and magnesium hydroxide solutions were then mixed evenly, an appropriate amount of dispersant was added, and the mixture was stirred using a high-speed shear emulsifier for 10 minutes. The fabric substrate was immersed in the flame-retardant dispersion for 20 minutes, removed and the excess solution scraped off. The fabric was initially dried at 100°C and then cured at 150°C for 30 minutes. Both the nano-silica and nano-magnesium hydroxide particles were modified with a silane coupling agent.
[0063] S2: After mixing and stirring the various components of the catalyst coating in proportion, the catalyst coating is applied to the surface of the fabric treated in step S1 by brushing or dipping at 100°C for 20 minutes; S3: After mixing the various components of the catalyst coating in proportion, stir at a low speed for 2 hours, then let it stand and mature for 1 hour, use a spraying device to evenly spray the solution on the fabric treated in step S1, and place it in a 100°C oven to dry for 1 hour.
[0064] Example 8 A flame-retardant fiber curtain fabric comprises a fabric base and a flame-retardant coating, a catalyst coating and a self-repairing coating sequentially arranged on the fabric base, wherein the flame-retardant coating comprises nano-silicon dioxide particles and nano-magnesium hydroxide particles in a mass ratio of 1:2.
[0065] The catalyst coating is prepared by including the following components in parts by weight: 4 parts of titanium dioxide; 2 parts of zirconium phosphate; 0.8 parts of coupling agent; 3 parts of polyvinyl alcohol; 95 parts of deionized water.
[0066] The self-repairing coating includes the following components in parts by weight: 8 parts of polyethylene glycol; 3 parts of furan-based polyamide elastomer; 30 parts of dimethylformamide; 9 parts of bismaleimide resin; 4 parts of ammonium polyphosphate.
[0067] The thickness of the flame retardant coating is controlled to be 300 μm.
[0068] The thickness of the catalyst coating is controlled to be 200 μm.
[0069] The thickness of the self-repairing coating is controlled to be 200 μm.
[0070] A method for preparing the flame-retardant fiber curtain fabric comprises the following steps: S1: Nano-silica and nano-magnesium hydroxide were placed separately in deionized water containing a silane coupling agent (KH-550) and ultrasonically treated for 30 minutes to achieve uniform dispersion and surface modification. The modified nano-silica and magnesium hydroxide solutions were then mixed evenly, an appropriate amount of dispersant was added, and the mixture was stirred using a high-speed shear emulsifier for 10 minutes. The fabric substrate was immersed in the flame-retardant dispersion for 20 minutes, removed and the excess solution scraped off. The fabric was initially dried at 100°C and then cured at 150°C for 30 minutes. Both the nano-silica and nano-magnesium hydroxide particles were modified with a silane coupling agent.
[0071] S2: After mixing and stirring the various components of the catalyst coating in proportion, the catalyst coating is applied to the surface of the fabric treated in step S1 by brushing or dipping at 100°C for 20 minutes; S3: After mixing the various components of the catalyst coating in proportion, stir at low speed for 2 hours, then let it stand and mature for 1 hour, use a spraying device to evenly spray the solution on the fabric treated in step S1, and place it in a 60°C oven to dry for 2 hours.
[0072] Example 9 A flame-retardant fiber curtain fabric comprises a fabric base and a flame-retardant coating, a catalyst coating and a self-repairing coating sequentially arranged on the fabric base, wherein the flame-retardant coating comprises nano-silicon dioxide particles and nano-magnesium hydroxide particles in a mass ratio of 1:2.
[0073] The catalyst coating is prepared by including the following components in parts by weight: 2 parts of titanium dioxide; 1 part zirconium phosphate; 0.3 parts of coupling agent; 1 part of polyvinyl alcohol; 90 parts of deionized water.
[0074] The self-repairing coating includes the following components in parts by weight: 12 parts of polyethylene glycol; 5 parts of furan-based polyamide elastomer; 50 parts of dimethylformamide; 11 parts of bismaleimide resin; 6 parts of ammonium polyphosphate.
[0075] The thickness of the flame retardant coating is controlled to be 400 μm.
[0076] The thickness of the catalyst coating is controlled to be 100 μm.
[0077] The thickness of the self-repairing coating is controlled to be 300 μm.
[0078] A method for preparing the flame-retardant fiber curtain fabric comprises the following steps: S1: Nano-silica and nano-magnesium hydroxide were placed separately in deionized water containing a silane coupling agent (KH-550) and ultrasonically treated for 30 minutes to achieve uniform dispersion and surface modification. The modified nano-silica and magnesium hydroxide solutions were then mixed evenly, an appropriate amount of dispersant was added, and the mixture was stirred using a high-speed shear emulsifier for 10 minutes. The fabric substrate was immersed in the flame-retardant dispersion for 20 minutes, removed and the excess solution scraped off. The fabric was initially dried at 100°C and then cured at 150°C for 30 minutes. Both the nano-silica and nano-magnesium hydroxide particles were modified with a silane coupling agent.
[0079] S2: After mixing and stirring the various components of the catalyst coating in proportion, the catalyst coating is applied to the surface of the fabric treated in step S1 by brushing or dipping at 100°C for 20 minutes; S3: After mixing the various components of the catalyst coating in proportion, stir at a low speed for 2 hours, then let it stand and mature for 1 hour, use a spraying device to evenly spray the solution on the fabric treated in step S1, and place it in a 100°C oven to dry for 2 hours.
[0080] Example 10 A flame-retardant fiber curtain fabric comprises a fabric base and a flame-retardant coating, a catalyst coating and a self-repairing coating sequentially arranged on the fabric base, wherein the flame-retardant coating comprises nano-silicon dioxide particles and nano-magnesium hydroxide particles in a mass ratio of 1:2.
[0081] The catalyst coating is prepared by including the following components in parts by weight: 2 parts of titanium dioxide; 1 part zirconium phosphate; 0.3 parts of coupling agent; 0.5 parts of borate; 1 part of polyvinyl alcohol; 90 parts of deionized water.
[0082] The self-repairing coating includes the following components in parts by weight: 12 parts of polyethylene glycol; 5 parts of furan-based polyamide elastomer; 50 parts of dimethylformamide; 11 parts of bismaleimide resin; 6 parts of ammonium polyphosphate.
[0083] The thickness of the flame retardant coating is controlled to be 400 μm.
[0084] The thickness of the catalyst coating is controlled to be 100 μm.
[0085] The thickness of the self-repairing coating is controlled to be 300 μm.
[0086] A method for preparing the flame-retardant fiber curtain fabric comprises the following steps: S1: Nano-silica and nano-magnesium hydroxide were placed separately in deionized water containing a silane coupling agent (KH-550) and ultrasonically treated for 30 minutes to achieve uniform dispersion and surface modification. The modified nano-silica and magnesium hydroxide solutions were then mixed evenly, an appropriate amount of dispersant was added, and the mixture was stirred using a high-speed shear emulsifier for 10 minutes. The fabric substrate was immersed in the flame-retardant dispersion for 20 minutes, removed and the excess solution scraped off. The fabric was initially dried at 100°C and then cured at 150°C for 30 minutes. Both the nano-silica and nano-magnesium hydroxide particles were modified with a silane coupling agent.
[0087] S2: After mixing and stirring the various components of the catalyst coating in proportion, the catalyst coating is applied to the surface of the fabric treated in step S1 by brushing or dipping at 100°C for 20 minutes; S3: After mixing the various components of the catalyst coating in proportion, stir at a low speed for 2 hours, then let it stand and mature for 1 hour, use a spraying device to evenly spray the solution on the fabric treated in step S1, and place it in a 100°C oven to dry for 2 hours.
[0088] Example 11 A flame-retardant fiber curtain fabric comprises a fabric base and a flame-retardant coating, a catalyst coating and a self-repairing coating sequentially arranged on the fabric base, wherein the flame-retardant coating comprises nano-silicon dioxide particles and nano-magnesium hydroxide particles in a mass ratio of 1:2.
[0089] The catalyst coating is prepared by including the following components in parts by weight: 2 parts of titanium dioxide; 1 part zirconium phosphate; 0.3 parts of coupling agent; 1 part borate; 1 part of polyvinyl alcohol; 90 parts of deionized water.
[0090] The self-repairing coating includes the following components in parts by weight: 12 parts of polyethylene glycol; 5 parts of furan-based polyamide elastomer; 50 parts of dimethylformamide; 11 parts of bismaleimide resin; 6 parts of ammonium polyphosphate.
[0091] The thickness of the flame retardant coating is controlled to be 400 μm.
[0092] The thickness of the catalyst coating is controlled to be 100 μm.
[0093] The thickness of the self-repairing coating is controlled to be 300 μm.
[0094] A method for preparing the flame-retardant fiber curtain fabric comprises the following steps: S1: Nano-silica and nano-magnesium hydroxide were placed separately in deionized water containing a silane coupling agent (KH-550) and ultrasonically treated for 30 minutes to achieve uniform dispersion and surface modification. The modified nano-silica and magnesium hydroxide solutions were then mixed evenly, an appropriate amount of dispersant was added, and the mixture was stirred using a high-speed shear emulsifier for 10 minutes. The fabric substrate was immersed in the flame-retardant dispersion for 20 minutes, removed and the excess solution scraped off. The fabric was initially dried at 100°C and then cured at 150°C for 30 minutes. Both the nano-silica and nano-magnesium hydroxide particles were modified with a silane coupling agent.
[0095] S2: After mixing and stirring the various components of the catalyst coating in proportion, the catalyst coating is applied to the surface of the fabric treated in step S1 by brushing or dipping at 100°C for 20 minutes; S3: After mixing the various components of the catalyst coating in proportion, stir at a low speed for 2 hours, then let it stand and mature for 1 hour, use a spraying device to evenly spray the solution on the fabric treated in step S1, and place it in a 100°C oven to dry for 2 hours.
[0096] Example 12 A flame-retardant fiber curtain fabric comprises a fabric base and a flame-retardant coating, a catalyst coating and a self-repairing coating sequentially arranged on the fabric base, wherein the flame-retardant coating comprises nano-silicon dioxide particles and nano-magnesium hydroxide particles in a mass ratio of 1:2.
[0097] The catalyst coating is prepared by including the following components in parts by weight: 2 parts of titanium dioxide; 1 part zirconium phosphate; 0.3 parts of coupling agent; 1.5 parts of borate; 1 part of polyvinyl alcohol; 90 parts of deionized water.
[0098] The self-repairing coating includes the following components in parts by weight: 12 parts of polyethylene glycol; 5 parts of furan-based polyamide elastomer; 50 parts of dimethylformamide; 11 parts of bismaleimide resin; 6 parts of ammonium polyphosphate.
[0099] The thickness of the flame retardant coating is controlled to be 400 μm.
[0100] The thickness of the catalyst coating is controlled to be 100 μm.
[0101] The thickness of the self-repairing coating is controlled to be 300 μm.
[0102] A method for preparing the flame-retardant fiber curtain fabric comprises the following steps: S1: Nano-silica and nano-magnesium hydroxide were placed separately in deionized water containing a silane coupling agent (KH-550) and ultrasonically treated for 30 minutes to achieve uniform dispersion and surface modification. The modified nano-silica and magnesium hydroxide solutions were then mixed evenly, an appropriate amount of dispersant was added, and the mixture was stirred using a high-speed shear emulsifier for 10 minutes. The fabric substrate was immersed in the flame-retardant dispersion for 20 minutes, removed and the excess solution scraped off. The fabric was initially dried at 100°C and then cured at 150°C for 30 minutes. Both the nano-silica and nano-magnesium hydroxide particles were modified with a silane coupling agent.
[0103] S2: After mixing and stirring the various components of the catalyst coating in proportion, the catalyst coating is applied to the surface of the fabric treated in step S1 by brushing or dipping at 100°C for 20 minutes; S3: After mixing the various components of the catalyst coating in proportion, stir at a low speed for 2 hours, then let it stand and mature for 1 hour, use a spraying device to evenly spray the solution on the fabric treated in step S1, and place it in a 100°C oven to dry for 2 hours.
[0104] Example 13 A flame-retardant fiber curtain fabric comprises a fabric base and a flame-retardant coating, a catalyst coating and a self-repairing coating sequentially arranged on the fabric base, wherein the flame-retardant coating comprises nano-silicon dioxide particles and nano-magnesium hydroxide particles in a mass ratio of 1:2.
[0105] The catalyst coating is prepared by including the following components in parts by weight: 2 parts of titanium dioxide; 1 part zirconium phosphate; 0.3 parts of coupling agent; 1 part borate; 1 part of polyvinyl alcohol; 90 parts of deionized water.
[0106] The self-repairing coating includes the following components in parts by weight: 12 parts of polyethylene glycol; 5 parts of furan-based polyamide elastomer; 50 parts of dimethylformamide; 11 parts of bismaleimide resin; 0.1 parts of copper oxide; 6 parts of ammonium polyphosphate.
[0107] The thickness of the flame retardant coating is controlled to be 400 μm.
[0108] The thickness of the catalyst coating is controlled to be 100 μm.
[0109] The thickness of the self-repairing coating is controlled to be 300 μm.
[0110] A method for preparing the flame-retardant fiber curtain fabric comprises the following steps: S1: Nano-silica and nano-magnesium hydroxide were placed separately in deionized water containing a silane coupling agent (KH-550) and ultrasonically treated for 30 minutes to achieve uniform dispersion and surface modification. The modified nano-silica and magnesium hydroxide solutions were then mixed evenly, an appropriate amount of dispersant was added, and the mixture was stirred using a high-speed shear emulsifier for 10 minutes. The fabric substrate was immersed in the flame-retardant dispersion for 20 minutes, removed and the excess solution scraped off. The fabric was initially dried at 100°C and then cured at 150°C for 30 minutes. Both the nano-silica and nano-magnesium hydroxide particles were modified with a silane coupling agent.
[0111] S2: After mixing and stirring the various components of the catalyst coating in proportion, the catalyst coating is applied to the surface of the fabric treated in step S1 by brushing or dipping at 100°C for 20 minutes; S3: After mixing the various components of the catalyst coating in proportion, stir at a low speed for 2 hours, then let it stand and mature for 1 hour, use a spraying device to evenly spray the solution on the fabric treated in step S1, and place it in a 100°C oven to dry for 2 hours.
[0112] Example 14 A flame-retardant fiber curtain fabric comprises a fabric base and a flame-retardant coating, a catalyst coating and a self-repairing coating sequentially arranged on the fabric base, wherein the flame-retardant coating comprises nano-silicon dioxide particles and nano-magnesium hydroxide particles in a mass ratio of 1:2.
[0113] The catalyst coating is prepared by including the following components in parts by weight: 2 parts of titanium dioxide; 1 part zirconium phosphate; 0.3 parts of coupling agent; 1 part borate; 1 part of polyvinyl alcohol; 90 parts of deionized water.
[0114] The self-repairing coating includes the following components in parts by weight: 12 parts of polyethylene glycol; 5 parts of furan-based polyamide elastomer; 50 parts of dimethylformamide; 11 parts of bismaleimide resin; 0.2 parts of copper oxide; 6 parts of ammonium polyphosphate.
[0115] The thickness of the flame retardant coating is controlled to be 400 μm.
[0116] The thickness of the catalyst coating is controlled to be 100 μm.
[0117] The thickness of the self-repairing coating is controlled to be 300 μm.
[0118] A method for preparing the flame-retardant fiber curtain fabric comprises the following steps: S1: Nano-silica and nano-magnesium hydroxide were placed separately in deionized water containing a silane coupling agent (KH-550) and ultrasonically treated for 30 minutes to achieve uniform dispersion and surface modification. The modified nano-silica and magnesium hydroxide solutions were then mixed evenly, an appropriate amount of dispersant was added, and the mixture was stirred using a high-speed shear emulsifier for 10 minutes. The fabric substrate was immersed in the flame-retardant dispersion for 20 minutes, removed and the excess solution scraped off. The fabric was initially dried at 100°C and then cured at 150°C for 30 minutes. Both the nano-silica and nano-magnesium hydroxide particles were modified with a silane coupling agent.
[0119] S2: After mixing and stirring the various components of the catalyst coating in proportion, the catalyst coating is applied to the surface of the fabric treated in step S1 by brushing or dipping at 100°C for 20 minutes; S3: After mixing the various components of the catalyst coating in proportion, stir at a low speed for 2 hours, then let it stand and mature for 1 hour, use a spraying device to evenly spray the solution on the fabric treated in step S1, and place it in a 100°C oven to dry for 2 hours.
[0120] Example 15 A flame-retardant fiber curtain fabric comprises a fabric base and a flame-retardant coating, a catalyst coating and a self-repairing coating sequentially arranged on the fabric base, wherein the flame-retardant coating comprises nano-silicon dioxide particles and nano-magnesium hydroxide particles in a mass ratio of 1:2.
[0121] The catalyst coating is prepared by including the following components in parts by weight: 2 parts of titanium dioxide; 1 part zirconium phosphate; 0.3 parts of coupling agent; 1 part borate; 1 part of polyvinyl alcohol; 90 parts of deionized water.
[0122] The self-repairing coating includes the following components in parts by weight: 12 parts of polyethylene glycol; 5 parts of furan-based polyamide elastomer; 50 parts of dimethylformamide; 11 parts of bismaleimide resin; 0.3 parts of copper oxide; 6 parts of ammonium polyphosphate.
[0123] The thickness of the flame retardant coating is controlled to be 400 μm.
[0124] The thickness of the catalyst coating is controlled to be 100 μm.
[0125] The thickness of the self-repairing coating is controlled to be 300 μm.
[0126] A method for preparing the flame-retardant fiber curtain fabric comprises the following steps: S1: Nano-silica and nano-magnesium hydroxide were placed separately in deionized water containing a silane coupling agent (KH-550) and ultrasonically treated for 30 minutes to achieve uniform dispersion and surface modification. The modified nano-silica and magnesium hydroxide solutions were then mixed evenly, an appropriate amount of dispersant was added, and the mixture was stirred using a high-speed shear emulsifier for 10 minutes. The fabric substrate was immersed in the flame-retardant dispersion for 20 minutes, removed and the excess solution scraped off. The fabric was initially dried at 100°C and then cured at 150°C for 30 minutes. Both the nano-silica and nano-magnesium hydroxide particles were modified with a silane coupling agent.
[0127] S2: After mixing and stirring the various components of the catalyst coating in proportion, the catalyst coating is applied to the surface of the fabric treated in step S1 by brushing or dipping at 100°C for 20 minutes; S3: After mixing the various components of the catalyst coating in proportion, stir at a low speed for 2 hours, then let it stand and mature for 1 hour, use a spraying device to evenly spray the solution on the fabric treated in step S1, and place it in a 100°C oven to dry for 2 hours.
[0128] Comparative Example 1 A flame-retardant fiber curtain fabric comprises a fabric base and a flame-retardant coating arranged on the fabric base, wherein the flame-retardant coating is a nano-silicon dioxide particle coating.
[0129] A method for preparing the flame-retardant fiber curtain fabric comprises the following steps: S1: Mix nano-silica with an appropriate amount of dispersant using a high-speed shear emulsifier and stir for 10 minutes; immerse the fabric substrate in the flame retardant dispersion for 20 minutes, remove and scrape off excess solution; preliminarily dry at 100°C, and then cure at 150°C for 30 minutes.
[0130] Comparative Example 2 A flame-retardant fiber curtain fabric comprises a fabric base and a flame-retardant coating arranged on the fabric base, wherein the flame-retardant coating is a nano-silicon dioxide particle coating.
[0131] A method for preparing the flame-retardant fiber curtain fabric comprises the following steps: S1: Mix nano magnesium hydroxide particles with an appropriate amount of dispersant using a high-speed shear emulsifier and stir for 10 minutes; immerse the fabric base in the flame retardant dispersion for 20 minutes, remove and scrape off excess solution; preliminarily dry at 100°C, and then cure at 150°C for 30 minutes.
[0132] Detection method 1. Flame retardant test: GB / T 5455-2014 "Textiles - Determination of burning behavior - Vertical burning method" was used for testing. The test results are shown in Table 1. Definition of burning time: Burning time usually refers to the time from the sample contacting the fire source to the flame extinguishing, that is, the duration of the sample surface burning or melting.
[0133] 2. Self-repair test: The fabric was cut and heated to 80°C. The healing of the cracks was observed within 5 minutes, as shown in Table 2 below.
[0134] 3. Washing test: After 20 machine washes, the fabrics of Examples 1 to 15 still maintained more than 90% of the flame retardant performance and the complete coating structure.
[0135] The above test results show that the flame retardant fiber curtain fabric of the present invention greatly improves the flame retardant effect and thermal stability of the flame retardant fiber curtain fabric by superimposing the flame retardant coating, the catalyst coating and the self-repairing coating.
[0136] The above description is merely a preferred embodiment of the present invention. The scope of protection of the present invention is not limited to the above embodiment. All technical solutions based on the concept of the present invention are within the scope of protection of the present invention. It should be noted that for those skilled in the art, various improvements and modifications that do not depart from the principles of the present invention should also be considered within the scope of protection of the present invention.
Claims
1. A flame retardant fiber curtain fabric, characterized in that: The invention comprises a fabric base and a flame retardant coating arranged on the fabric base, wherein the flame retardant coating comprises nano silicon dioxide particles and nano magnesium hydroxide particles in a mass ratio of 1:1.2-2.
2. The flame retardant fiber curtain fabric according to claim 1, characterized in that: The flame retardant coating is also provided with a catalyst coating and a self-repairing coating, and the catalyst coating is prepared by including the following components in parts by weight: 2-4 parts of titanium dioxide; 1-2 parts of zirconium phosphate; 0.3-0.8 parts of coupling agent; 1-3 parts of polyvinyl alcohol; 90-95 parts of deionized water.
3. The flame retardant fiber curtain fabric according to claim 2, characterized in that: The self-repairing coating comprises the following components in parts by weight: 8-12 parts of polyethylene glycol; 3-5 parts of furan-based polyamide elastomer; 30-50 parts of dimethylformamide; 9-11 parts of bismaleimide resin; 4 to 6 parts of ammonium polyphosphate.
4. The flame retardant fiber curtain fabric according to claim 1, characterized in that: The nano silicon dioxide particles and nano magnesium hydroxide particles are both modified by a silane coupling agent.
5. The flame retardant fiber curtain fabric according to claim 2, characterized in that: The thickness of the flame retardant coating is controlled to be 300-400 μm.
6. The flame retardant fiber curtain fabric according to claim 2, characterized in that: The thickness of the catalyst coating is controlled to be 100-200 μm.
7. The flame retardant fiber curtain fabric according to claim 2, characterized in that: The thickness of the self-repairing coating is controlled to be 200-300 μm.
8. The flame retardant fiber curtain fabric according to claim 2, characterized in that: 0.5 to 1.5 parts by weight of borate is also added to the catalyst coating.
9. The flame retardant fiber curtain fabric according to claim 3, characterized in that: The self-repairing coating further contains 0.1 to 0.3 parts by weight of copper oxide.
10. A method for preparing the flame-retardant fiber curtain fabric according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1: Mix nano silicon dioxide and magnesium hydroxide evenly, add appropriate amount of dispersant, and stir with a high-speed shear emulsifier for 10 minutes; immerse the fabric base in the flame retardant dispersion for 20 minutes, take out and scrape off the excess solution; preliminarily dry at 100°C, and then cure at 150°C for 30 minutes; S2: After mixing and stirring the components of the catalyst coating in proportion, the catalyst coating is applied to the surface of the fabric treated in step S1 by brushing or dipping at 100°C for 20 minutes; S3: After mixing the various components of the catalyst coating in proportion, stir at a low speed for 2 to 3 hours, then let it stand for 1 to 2 hours, use a spraying device to evenly spray the solution on the fabric treated in step S1, and place it in an oven at 60 to 100°C to dry for 1 to 2 hours.
Citation Information
Patent Citations
Microencapsulation expansion type flame retardant and application in epoxy resin composite material thereof
CN101812186A
High oil-content thermoplastic elastomer SEBS flame retardant composite and preparation method thereof
CN101974196A
Semi-biomass furyl soluble aromatic polyamide and preparation method and application thereof
CN105801843A
Preparation method of fire-resistant flame-retardant polyethylene fiber UD cloth
CN111074536A
Flame-retardant self-repairing coating and fire early warning application thereof
CN116516673A
Cited By
High-strength flame-retardant curtain fabric and processing technology thereof
CN120844372A
Roller shutter fabric and production process thereof
CN120925331A
A roller blind fabric and a production process thereof
CN120925331B
